2009
DOI: 10.1209/0295-5075/87/26005
|View full text |Cite
|
Sign up to set email alerts
|

Local structure of ReFeAsO (Re=La, Pr, Nd, Sm) oxypnictides studied by Fe K-edge EXAFS

Abstract: Local structure of REOFeAs (RE=La, Pr, Nd, Sm) system has been studied as a function of chemical pressure varied due to different rare-earth size. Fe K-edge extended X-ray absorption fine structure (EXAFS) measurements in the fluorescence mode has permitted to compare systematically the inter-atomic distances and their mean square relative displacements (MSRD). We find that the Fe-As bond length and the corresponding MSRD hardly show any change, suggesting the strongly covalent nature of this bond, while the F… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
47
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 28 publications
4
47
0
Order By: Relevance
“…The opening angle at the top of the Fe 4 As tetrahedron is estimated to be 113.2°for SC CeFeAsO 1−y and 115.33°for non-SC CeFeAsO 1−y by using the relation of ␣ = − 2 cos −1 ͑d Fe-Fe / ͱ 2d Fe-As ͒, where d is the distance between the atoms. 42 The Fe-As-Fe angle of the SC CeFeAsO 1−y is closer to the perfect tetrahedron angle of 109.5°than that of the non-SC CeFeAsO 1−y , as suggested by Lee et al 20 The vertical height of As from the Fe-Fe plane is about 1.31 Å for SC CeFeAsO 1−y and 1.26 Å for non-SC CeFeAsO 1−y . Our results are consistent with the idea that T C is maximum around the pnictogen height of 1.38 Å in the Fe-based SC.…”
Section: B Exafsmentioning
confidence: 53%
“…The opening angle at the top of the Fe 4 As tetrahedron is estimated to be 113.2°for SC CeFeAsO 1−y and 115.33°for non-SC CeFeAsO 1−y by using the relation of ␣ = − 2 cos −1 ͑d Fe-Fe / ͱ 2d Fe-As ͒, where d is the distance between the atoms. 42 The Fe-As-Fe angle of the SC CeFeAsO 1−y is closer to the perfect tetrahedron angle of 109.5°than that of the non-SC CeFeAsO 1−y , as suggested by Lee et al 20 The vertical height of As from the Fe-Fe plane is about 1.31 Å for SC CeFeAsO 1−y and 1.26 Å for non-SC CeFeAsO 1−y . Our results are consistent with the idea that T C is maximum around the pnictogen height of 1.38 Å in the Fe-based SC.…”
Section: B Exafsmentioning
confidence: 53%
“…Recently, in this class of materials, it was found that oxygen ordering plays a critical role in determining the macroscopic properties of the system [1][2][3]. In fact, our own research works in diverse materials such as hydrogen storage materials [4], lithium battery materials [5], several nano-material systems [6][7][8], newly discovered Fe-based superconductors [9][10][11][12], novel magnetic materials [13,14] and solar cell materials [15], etc., were indeed aimed at understanding the structure-function relations. Black phosphorus (BP) is an emerging two-dimensional system offering several perspectives for applications.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, the FeSe (the 11-type chalcogenide) shows lowest superconducting transition temperature (T c ∼8 K), however, could be considered as a model system to address basic characteristics of these materials [3]. The FeSe structure contains simple stacking of tetrahedrally coordinated FeSe 4 layers without spacer layers that are known to have substantial effect on the electronic properties [4,5]. Susbstitution by Te in the FeSe leads to a marginal increase in the T c (∼ 15 K), however, the system gets phase separated and the nanoscale structure is characterized by different iron-chalcogen bondlengths [8].…”
Section: Introductionmentioning
confidence: 99%
“…EXAFS has also been exploited to study the new iron-based superconductors, revealing important information on the atomic correlations between different layers [4,5] and temperature dependent local structural anomalies across the superconducting transition [25,26]. More recently, we have applied EXAFS to study the local structure of FeSe 1−x Te x chalcogenides, providing direct evidence of phase separation in the ternary systems, characterized by different Fe-Se and Fe-Te distances [8].…”
Section: Introductionmentioning
confidence: 99%